KARDİYOPULMONER BYPASS EŞLİĞİNDE KORONER ARTER BYPASS GREFT UYGULANAN OLGULARDA SİSTEMİK ENFLAMATUAR YANITIN AZALTILMASINDA OLMESARTAN MEDOKSİMİLİN ETKİNLİĞİ - KILINÇ, ABDULGANİ (Fırat Üniveristesi, 2012)
Kardiyopulmoner bypass (KPB) ile koroner arter bypass greft (KABG) cerrahisi sonrası sistemik enflamatuar yanıt sendromu (SIRS) sıklıkla gözlenir. Anjiotensin II reseptör blokeri olan olmesartan'ın enflamatuar etkileri azalttığı bilinmektedir. Bu çalışmada KPB uygulanan hastalarda olmesartan tedavisinin SIRS'a etkisi araştırıldı.Çalışmaya 30-80 yaş arası, KABG uygulanacak 50 hasta (kadın: 14, erkek: 36) alındı, hastalar randomize 2 gruba ayrıldı, (Grup K: Kontrol, Grup O: Olmesartan). Grup K'daki hastalara herhangi bir tedavi uygulanmadı. Grup O'daki hastalara preoperatif 5 gün önceden başlayıp postoperatif 35. güne kadar 10 mg/gün, günde tek doz, operasyon günü 30 mg olmesartan verildi. Tüm hastalardan anestezi indüksiyonu öncesi (T1), kros klemp konduktan 5 dk sonra (T2), kros klemp alındıktan 5 dk sonra (T3), protamin infüzyonu sonrası (T4), postoperatif 3. gün (T5) ve postoperatif 35. gün (T6) olmak üzere altı dönemde kan alınarak IL-6, IL-10 ve IL-18'in serum düzeyleri incelendi. Ayrıca preoperatif (T1) ve postoperatif 35. gün (T2) serum örneğinde h-CRP düzeyleri değerlendirildi.Olmesartan alanlarda h-CRP düzeylerinin postoperatif 35. gün anlamlı olarak azaldığı saptandı (p<0.05). Her iki grupta IL-6 düzeylerinin indüksiyon öncesi döneme göre diğer dönemlerde anlamlı arttığı (p<0.05), tüm hastalarda IL-10 düzeylerinin operasyon süresince anlamlı olmak üzere gittikçe arttığı, postoperatif dönemde azalmasına rağmen bazal değerlere göre yüksek olduğu (p<0.05), IL-18 düzeylerinin ise her iki grupta bazal değerlere göre arttığı (p<0.05), bu artışın olmesartan grubunda daha belirgin olduğu saptandı (p<0.05).KABG operasyonu uygulananlarda olmesartan uygulanmasının IL-6 ve IL-18'in etkilerini ve düzeylerini azaltmadığı, IL-10 düzeylerini artırdığı, özellikle postoperatif dönemde enflamatuar yanıtı (h-CRP) azaltarak gelişebilecek postoperatif komplikasyonların azaltılabileceği kanaatine varıldı.Anahtar Kelimeler: Sistemik enflamatuar yanıt sendromu, h-CRP, İnterlökin-6, İnterlökin-10, İnterlökin-18.

Systemic inflammatory response syndrome (SIRS) is common following coronary artery bypass graft (CABG) surgery with cardiopulmonary bypass (CPB). It is known that olmesartan, an angiotensin II receptor blocker, reduces the inflammatory reactions. In this study, the effect of olmesartan therapy in patients undergoing CBP was evaluated on SIRS in patients undergoing CBP.The study included 50 patients (14 women, 36 men) aged between 30 and 80 years, those were randomly divided into two groups (Group K: control; Group O: olmesartan). Patients in the group K were not given any treatment. Patients in the group O were administered olmesartan 10 mg/day as daily single dose beginning preoperatively 5 days before the surgery and continuing until postoperative day 35; patients in this group were given 30 mg olmesartan on the day of surgery. Six blood specimens were collected from each patient in different times, prior to the induction of anesthesia (T1), 5 minutes after the insertion of cross clamp (T2), 5 minutes after the removal of cross clamp (T3), after protamine infusion (T4), on the postoperative day 3 (T5), and on the postoperative day 35 (T6). Serum levels of IL-6, IL-10 and IL-18 were analyzed in each specimen. The level of h-CRP was also determined in preoperative basal (T1) and postoperative day 35 (T2) serum specimens.It was found that h-CRP levels of the patients given olmesartan reduced significantly on the postoperative day 35 (p<0.05). In both groups, it was observed that in comparison with the period prior to the induction, IL-6 levels significantly increased in other periods (p<0.05). It was found that IL-10 level increased gradually and significantly during the surgery in all patients, in the postoperative period, although it reduced, it was still higher than basal level (p<0.05). It was observed that IL-18 level increased in both groups in comparison with basal levels (p<0.05) and this increase was more remarkable in olmesartan group (p<0.05).We concluded that the use of olmesartan in CABG operations did not reduce levels and effects of IL-6, IL-18, but increased levels of IL-10 and decreased possible complications especially with decreasing inflammatory responce (h-CRP) in postoperative period.Keywords: Systemic inflammatory response syndrome, h-CRP, Interleukin-6, Interleukin-10, Interleukin-18
The effectivenes of the olmesartan medoximil in reducing the systemic inflammatory response in patients undergoing coronary artery bypass grafting with cardiopulmonary bypass device
Keywords: Göğüs Kalp ve Damar Cerrahisi